Value Added Tax Evasion, Auditing and Transactions Matching - Ira N. Gang; Arindam Das-Gupta (Rutgers University, Department of Economics, 1998)
This paper extends the standard theoretical model of tax enforcement by allowing for the cross- matching of transactions in addition to the auditing of taxpayers. For the Value Added Tax (VAT) the matching of purchase and sales invoices is an important enforcement technique. The paper examines the impact such enforcement on the revenue effectiveness and efficiency consequences of the VAT. Transactions matching is shown to have very different effects from auditing: Even when auditing alone is unable to induce non-zero taxpayer reports, and regardless of the expected success rate in auditing of the tax administration, sufficiently intensive cross- matching can induce truthful reporting. On the other hand, matching leads to distorted purchase and sales transactions. It can also distort input use and output decisions even if auditing alone has no adverse effects. In the model, conditions under which the VAT leaves input prices undistorted are found and the content of the often made claim, that a VAT is self-enforcing, is explored. The ability of the tax administration to enforce compliance with the VAT is shown to be sensitive to the knowledge that the tax administration has about the production technology.
Keywords: 330